Pyrometry of the processes of self-propagating high-temperature synthesis; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 2 - Gumirov M. A. (Mathematics and mechanics.Physics, 2007)
Заглавие с титульного листа